Investigation of Analysis Methods For Detection of Humic Substances Within Leonardite: Investigation of Analysis Methods For Detection of Humic Substances Within Leonardite - Canıeren, Ömer; Karagüzel, Cengiz; Aydın, Ahmet (International Journal of Economic and Environmental Geology, 2018)
Leonardite is a lignite form, which has undergone oxidation at high rate during the carbonization process. It has economic value because it contains humic substances at high rate. While it is used in organic agriculture, as soil conditioner, it is also used in other industrial fields such as cosmetics and medicine. Physical properties such as color, as well as chemical properties such as solubility in alkaline media and humic content are examined for the definition and characterization of leonardite. In particular, the detection of humic substance content is the most important feature used in the industrial usage of leonardites. Various instrumental analysis techniques and wet chemical analysis techniques are utilized for this purpose. However, it is a matter of debate whether these methods are applicable for the industry. In this study, instrumental and chemical methods used in the analysis of humic substance were examined. Along with these, industrial, reliable and fast methods have been determined as well.